Methods of Betulin Extraction from Birch Bark - Demets, O.V.; Takibayeva, A.T.; Kassenov, R.Z; Aliyeva, M.R. (Molecules, 2022)
Betulin is the most popular of the known triterpenoids of the lupan series. It has valuable pharmacological properties. It exhibits antibacterial, antiviral, antitumor, hypolipidemic and other types of activity. The prospects of using betulin in medicine, pharmacology, and veterinary medicine require the development of effective methods for obtaining it from waste from the woodworking industry. Therefore, the question arises of the need to develop a technology for isolating and purifying triterpenoids from birch bark in large quantities. This review contains a variety of methods for the isolation of betulin. The advantages and disadvantages of the proposed methods are described. The following methods are considered: vacuum sublimation after preliminary alkaline; vacuum pyrolysis; supercritical extraction with carbon dioxide or mixtures of carbon dioxide with various solvents; extraction with organic solvents. Also, the method of microwave is described, it is activation on the example of the Kyrgyz birch (Betula kirghisorum), this is an endemic species that has not been studied before, growing on the territory of the Republic of Kazakhstan.
Keywords: betulin; birch bark; pentacyclic triterpenoid; biological activity; methods of betulin isolation